Economic safety problem in modern macro and micro concepts - Rekun, I. I. (Science and Transport Progress, 2014)
Purpose. Security is an important component of economic security and the guaranteeing of appropriate national interests in the state. All these things are closely related to the economic efficiency of operations of economic entities, with economic independence, stability and security of a society. In addition, economic security is a part of national security, its foundation and material basis. The problem of economic security in modern conditions at the micro and macro levels requires determining the main directions of its formation. Methodology. To achieve this goal, basic directions of a security mechanism of the economic system, in particular on the macro level were grounded. Findings. Economic security is such state of the state economy operation in which the order of equilibrium occurred in certain organizational and legal norms on the basis of social life. These regulations are created be the state, principles of coexistence, which are transmitted from generation to generation. The current state of economic security guaranteeing at the macro and micro levels was analyzed. The system of indicators that can be used in the assessment of the security system was determined. Originality. Propositions concerning necessary changes in the policy of economic security in a state were formulated. The system of indicators which can be used in the assessment of the security system was offered. Practical value. Using of the proposed system of economic security indicators will expand the list of important factors affecting on its status and allow us determining the main directions of its formation.